Uso de pastagem de gramíneas de estação quente na recria de novilhas de corte - Souza, Alexandre Nunes Motta de (2009)
The experiment was carried out to evaluate attributes of pastures and relazed to ingestive behavior, the animal performance and reproduction of beef heifers reared from 15 to 18 months and bred at 18/20 months of age. In observations of ingestive behavior were evaluated heifers on Pearl millet (Pennisetum americanum) and alexandergrass (Urochloa plantaginea). The experimental design was complete randomized following a repeated measure arrangement, with two treatments and two replications. The grazing method was continuous with variable stocking rate in order to maintain the sward height at 40 cm. The leaf, stem and dead material masses, rate of herbage accumulation, leaf/stem relation, leaf and herbage on offer, neutral detergent fiber were similar between Pearl millet and alexandergrass. The ingestive behavior of heifers, measured by grazing, rumination and idle times, bite rate, bite weight, bite by feeding station, feeding stations per minute and rate of displacement was similar when kept in pearl millet or alexandergrass. In performance and reproduction evaluations, in addition to Pearl millet and alexandergrass, it was also evaluated heifers on native pastures invaded by Annoni-2 grass (Eragrostis plana Nees). The differences between the summer annual species (Pearl millet and alexandergrass) and Annoni- 2 grass were tested by contrast analysis. The attributes evaluated in the pasture were different between the annual summer species and Annoni-2 grass. The average daily gain, stocking rate, live weight gain per hectare, body weight, body condition score, weight to height ratio and reproductive tract score of the heifers at 18 months kept on annual summer pastures were superior, compared to the heifers on Annoni-2 grass pasture and resulted in different rates of pregnancy, with values of 75 and 25% respectively.